Defining the thermal boundary condition for protective structures in fire. (15th October 2017) - Torero, José L.; Law, Angus; Maluk, Cristian
Highlights: The thermal solicitation for fire events is defined in terms of heat flux. The transfer of heat into a structure is analysed, and the reliance of the Biot number is explored. The equations for heat transfer are expressed for the steady state and in terms of the Biot number. The impact of the Biot number on the transient and steady state structural response is analysed and compared. Abstract: Protective structures are designed explicitly to fulfil a function that in many cases is an extreme event; therefore, an explicit design has to properly and precisely account for the nature of the solicitation imposed by the extreme event. Extreme events such as explosions or earthquakes are reduced to design criteria on the basis of either empirical or historical data. To determine the design criteria, the physical data has to be translated into physical variables (amplitudes, pressures, frequencies, etc.) that are then imposed to the protective structure. While there is debate on the precision and comprehensive nature of this translation, years of research have provided strong physical arguments in supporting these methods. Performance is then quantified on the basis of the structure's capability to perform its required function. Classified solicitations may then be used to translate performance into prescribed requirements that provide an implicitly high confidence that the structure performs its function. When addressing fire, performance has been traditionally determined by imposing standardized requirements that necessarily attempt to bear a strong relationship with the reality of potential events – the fire performance of a protective structure is thus defined as a fire resistance period. This paper addresses the concept of fire resistance and its relevance to the design of protective structures. The mathematical description of the thermal boundary conditions for a fire is of extreme complexity, therefore simplified approaches, that include the Fire Resistance concept, are currently used. By using classical heat transfer and structural engineering arguments, the work described herein demonstrates that an adequate level of complexity and precision for the thermal boundary conditions and input parameter is fundamental to correctly describe the response of a structure during a fire event. Simple criteria are presented to qualify the relevance of current approaches and to highlight important issues to be considered.